The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4269/ajtmh.17-0698
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Clinical Trial to Evaluate Ivermectin in the Reduction of Mansonella ozzardi infection in the Brazilian Amazon

Abstract: The treatment of mansonelliasis is still a challenge because there are few clinical trials for the treatment of the disease. This double-blind, randomized, placebo-controlled study (phase III clinical trial) was conducted to evaluate the effectiveness of a single oral dose of ivermectin (0.15 mg/kg) in the reduction of the microfilaraemia and the occurrence of adverse effects in infected people compared with the control group treated with placebo. A total of 49 microfilaraemic patients were randomly selected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The targets of ivermectin as identified through genetic studies in C. elegans include various subunits of the GlutamateLgated Cl− channels (GluCl), encoded by genes glc-1 , glc-2 , glc-3 , glc-4 , avr-14 and avr-15 (Dent et al, 2000; Wolstenholme and Rogers, 2005). Ivermectin is effective in treating M. ozzardi infections (Basano et al, 2018), but is reported to be ineffective against M. perstans (Bregani et al, 2006). Phylogenetic analysis of these genes across filarial parasites shows that the homologs of glc-1 , glc-2 , glc-3 , avr-14 and avr-15 form a family of paralogous genes with complex patterns of homology across filarial parasites (Figure 5), while glc-4 has one-to-one orthologs across all genomes analyzed (Supplementary Figure 13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The targets of ivermectin as identified through genetic studies in C. elegans include various subunits of the GlutamateLgated Cl− channels (GluCl), encoded by genes glc-1 , glc-2 , glc-3 , glc-4 , avr-14 and avr-15 (Dent et al, 2000; Wolstenholme and Rogers, 2005). Ivermectin is effective in treating M. ozzardi infections (Basano et al, 2018), but is reported to be ineffective against M. perstans (Bregani et al, 2006). Phylogenetic analysis of these genes across filarial parasites shows that the homologs of glc-1 , glc-2 , glc-3 , avr-14 and avr-15 form a family of paralogous genes with complex patterns of homology across filarial parasites (Figure 5), while glc-4 has one-to-one orthologs across all genomes analyzed (Supplementary Figure 13).…”
Section: Resultsmentioning
confidence: 99%
“…ozzardi infections (Basano et al, 2018), but is reported to be ineffective against M. perstans (Bregani et al, 2006). Phylogenetic analysis of these genes across filarial parasites shows that the homologs of glc-1, glc-2, glc-3, avr-14 and avr-15 form a family of paralogous genes with complex patterns of homology across filarial parasites (Figure 5), while glc-4 has one-to-one orthologs across all genomes analyzed (Supplementary Figure 13).…”
Section: Analysis and Comparison Of Genes Encoding Drug Targets For T...mentioning
confidence: 99%
“…Written informed consent was obtained from all patients or their parents or guardians if participants were minors aged <18 years. Diagnosed infections were treated with a single dose of 0.2 mg/kg of ivermectin after blood sampling ( De Almeida Basano et al 2018 ; Lima et al 2018 , 39).…”
Section: Methodsmentioning
confidence: 99%
“…Written informed consent was obtained from all patients, or their parents or guardians if participants were minors aged <18 years. Diagnosed infections were treated with a single dose of 0.2 mg/kg of ivermectin after blood sampling (Basano et al 2018; Lima et al 2018, 39).…”
Section: Methodsmentioning
confidence: 99%